PEMBERDAYAAN PETERNAK JANGKRIK DALAM MENGATASI HAMA ULAT UNTUK PENGUATAN EKONOMI LOKAL DI DESA PARENGAN MOJOKERTO - Maulidiya Putri Fatimah; Muhammad Anshori (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community empowerment activity was carried out with the cricket farming community in Parengan Village, Jetis District, Mojokerto Regency. The program aims to increase farmers’ capacity in controlling caterpillar pests that frequently reduce production. The implementation used the Asset Based Community Development (ABCD) method with five stages: Discovery, Dream, Design, Define, and Destiny. The empowerment process was participatory, involving training on natural pest control, demonstrations of herbal pesticide production, and field mentoring. The results showed that farmers became more disciplined in maintaining cleanliness, sterilizing cages, and using local natural materials such as soursop leaves and tobacco to control pests. Socially, the activity fostered collective awareness, the emergence of a local leader, and stronger solidarity among farmers. This empowerment program not only improved technical capabilities but also fostered social transformation, encouraging farmers to become more independent and sustainable in strengthening the local economy.